Effects of acidic phospholipids on antiganglioside antibodies in Guillain–Barré syndrome: Role of the disialosyl residue. Issue 1 (3rd December 2012) - Yamada, Minako H.; Ueda, Masami; Tsuji, Shoji; Kusunoki, Susumu
Abstract Objectives The activities of anti‐GM1 immunoglobulin G (IgG) antibodies in Guillain–Barré syndrome (GBS) are increased when a mixture of acidic phospholipids, such as phosphatidic acid (PA) and the ganglioside GM1, is used as an antigen in an enzyme‐linked immunosorbent assay (ELISA). In contrast, no obvious enhancing effect is seen on the activities of anti‐GQ1b antibodies in Fisher syndrome. The cause of these different results remains to be determined. We investigated whether it is caused by the difference in the pathogens of the preceding infections or by that in the physicochemical properties of GM1 and GQ1b. Methods The effects of the phospholipid on the antibody activities in ELISA were compared between the cases preceded by respiratory infections and those by gastrointestinal infections. We examined the effects of the phospholipids on anti‐GD1b IgG antibodies and compared the effects on GD1b‐specific antibodies and those on Gal‐GalNAc epitope‐specific antibodies. Results The effects of the phospholipids on the average of the antibody activities, either anti‐GM1 or anti‐GQ1b antibody, did not differ between patients with antecedent gastrointestinal infections and those with respiratory infections. The anti‐GD1b IgG activity in GBS patients with anti‐Gal‐GalNAc specificity increased when a mixture of GD1b and a phospholipid, such as PA, was an antigen; whereas the activity of monospecific anti‐GD1b IgG did not increase. Conclusions The enhancing effect of such a phospholipid as PA appears not to be a result of the presence of a particular phospholipid within the pathogen for the antecedent infection. It might depend on the presence of a negatively charged disialosyl residue in the ganglioside antigen.